JCU 2017 Reviewers (Journal of Clinical Ultrasound, 2018)
We hereby describe a new sonographic sign, the cardiac "flip" sign, to help in the prenatal detection of a right sided aortic arch with a right sided ductus arteriosus. This sign depends on pattern recognition where the sonologist/sonographer needs to obtain a cardiac sweep, commencing at the four chamber view and extending cephalad to the three vessel trachea view. In the normal heart there is a "flip" from the longitudinal axis of the heart, sweeping up to the level of the 3-vessel trachea view, and a line extending from the fetal chest and running in between the transverse arches. This "flip" is absent in case of a right aortic arch with a right ductus arteriosus.